2008
DOI: 10.1364/oe.16.012251
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast random laser emission in a dye-doped silica gel powder

Abstract: Abstract:We report efficient random lasing in a ground powder of a novel solid-state material based on silica gel containing SiO 2 nanoparticles embedding rhodamine 6G (Rh6G) dye. Basic properties of random lasing such as emission kinetics, emission spectrum, and threshold of stimulated emission are investigated by using real-time spectroscopy. The laser-like emission dynamics can be accurately described by a light diffusive propagation model. The device behavior is close to a conventional ultrafast Q-switched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 31 publications
(19 reference statements)
0
34
0
Order By: Relevance
“…[78,79] Laser emission is produced by multiple scattering processes that increase the dwell time of photons inside the material allowing amplification and creating gain saturation. [80] Random lasers were engineered to provide low spatial coherence and to generate images with superior quality than images generated with spatially coherent illumination.…”
Section: Random and Feedback Lasersmentioning
confidence: 99%
See 2 more Smart Citations
“…[78,79] Laser emission is produced by multiple scattering processes that increase the dwell time of photons inside the material allowing amplification and creating gain saturation. [80] Random lasers were engineered to provide low spatial coherence and to generate images with superior quality than images generated with spatially coherent illumination.…”
Section: Random and Feedback Lasersmentioning
confidence: 99%
“…[81,82] By providing intense laser illumination without the drawback of coherent artefacts (as those produced by lasers and superluminescent diodes that corrupt image formation), random lasers are well suited for full-field imaging applications, such as full-field microscopy and digital light projector systems. [82] With organic-inorganic hybrid materials, examples comprise ZnO nanoparticles dispersed into a polymer matrix, [83,84] Rh6G-doped SiO 2 nanoparticles, [78,85] Rh6G-bearing di-ureasils, [37,80] polymer films embedded with silver nanoparticles [86] and poly(2-hydroxyethyl methacrylate) (pHEMA) incorporating silsesquioxane nanoparticles (POSS) doped with the LDS722 and LDS730 red-emitting dyes. [87,88] Focusing on the example of Rh6G-bearing di-ureasils, the emission features of the ground powders were compared with those of a silica gel containing Rh6G-doped SiO 2 nanoparticles revealing a slightly larger slope efficiency and a lower threshold for laser-like emission in the later case (Figure 7).…”
Section: Random and Feedback Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacture details can be found in Ref. [24]. Ground powder of the silica gel with the Rh6G-SiO 2 nanoparticles was obtained by using a mixer mill.…”
Section: Methodsmentioning
confidence: 99%
“…The advantages of such a material are its solid-state nature, quenched disorder, high laser-like emission effi ciency, and the possibility of being functionalized for various applications in the fi eld of biosensors or biotracers. In a recent study, [ 21 ] the authors demonstrated random-laser action in a grown powder made of a silica gel containing 2 wt% Rh6G-SiO 2 nanoparticles and in a dispersed powder sample containing the same amount of fl uorescent nanoparticles. Moreover, we demonstrated that their random-laseremission dynamics can be accurately described by using a light-diffusive propagation model with the feedback provided by the powder.…”
Section: Research Newsmentioning
confidence: 99%